Application of Multisim Software in Wave Rectifier Circuit Learning and its influence based on Students' Visual Spatial Ability - Wahyudi, Wahyudi; Boisandi, Boisandi; Nurhayati, Nurhayati (UNIVERISTAS PGRI MADIUN, 2021)
This study aims to determine the effect of the National Instruments (NI) Multisim Software on students’ mastery of the wave rectifier circuit viewed from students' visual-spatial abilities (KVS). A pre-experimental design was used in this study. The sample of this research was students of the Physics Education Study Program taking the Basic Electronics I course selected through saturated sampling technique. The data collection tools were in the form of a visual-spatial ability test instrument and the wave rectifier circuit mastery test instrument. Correlation tests, multiple regression, and independent-sample t-test were used to determine the effect of spatial-visual ability on the learning outcomes of the wave rectifier circuit through the application of the National Instruments Multisim Software. The results obtained indicate that: 1) Student learning outcomes on the wave rectifier circuit material by using the NI-Multisim Software has in the sufficient category; 2) Students' visual-spatial ability on the KVS-interpretation has very high-category, KVS-series pattern has high-category, KVS-reflection has high-category, KVS-rotation has high-category, KVS-projection has high-category, and KVS-drawing has medium-category; 3) The ability of students' spatial visibility has a positive and significant correlation to student learning outcomes and has an influence contribution of 76.20% to learning outcomes; 4) The learning outcomes of students who have KVS-high are better than the average learning outcomes of students who have KVS-low in learning the wave rectifier series material using the NI-Multisim software.